2020
DOI: 10.3389/fpubh.2020.524356
|View full text |Cite
|
Sign up to set email alerts
|

Mortality From Alcohol-Related Liver Cirrhosis in Mexico (2000–2017)

Abstract: Background: Alcohol is the main cause of liver cirrhosis. The objective of this study was to analyze the mortality rates of alcohol-related cirrhosis in Mexico from 2000 to 2017. Methods: Mortality data from alcohol-related cirrhosis were obtained from the National Institute of Statistics and Geography. Rates were adjusted to the World Standard Population and were calculated with a direct method. The differences between genders were evaluated with Student's t-test, while the ANOVA test was used for differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…11 In concert with the liver cancer mortality findings, a recent study reported a statistically significant decrease in alcohol-related liver cirrhosis mortality in Mexico from 2000-2017. 19 The manuscript suggested that the reduction could be explained by a decrease in alcohol consumption from 1996 to 2004. 19 Despite this decline, cirrhosis remains of Mexico's leading causes of death.…”
Section: 95mentioning
confidence: 99%
See 1 more Smart Citation
“…11 In concert with the liver cancer mortality findings, a recent study reported a statistically significant decrease in alcohol-related liver cirrhosis mortality in Mexico from 2000-2017. 19 The manuscript suggested that the reduction could be explained by a decrease in alcohol consumption from 1996 to 2004. 19 Despite this decline, cirrhosis remains of Mexico's leading causes of death.…”
Section: 95mentioning
confidence: 99%
“…19 The manuscript suggested that the reduction could be explained by a decrease in alcohol consumption from 1996 to 2004. 19 Despite this decline, cirrhosis remains of Mexico's leading causes of death. 10 Our findings indicate that birth cohort may partially explain the overall reduction of liver cancer mortality.…”
Section: 95mentioning
confidence: 99%
“…En otro estudio se demostró que existe una buena tolerancia con el uso de probióticos puesto a que los pacientes no presentaron efectos adversos una vez administradas sin importar la dosis ingerida por los pacientes. Mouli et menciona que los probióticos han www.concienciadigital.org mejorado significativamente el índice de encefalopatía hepática y disminución de amoníaco en comparación a lactulosa después de dos meses de tratamiento, esto independientemente de la duración y de la dosis administrada (Yeverino-Gutiérrez et al, 2020).…”
Section: Tratamientounclassified
“…Se identifica por la fibrosis del hígado debido a una disminución del parénquima hepático que son reemplazados por nódulos hepáticos regenerativos y posterior a su necrosis (Velarde-Ruiz Velasco et al, 2022). Cualquier patología que ocasione una inflamación crónica en el hígado, con el transcurso del tiempo puede llegar a ocasionar cirrosis (Abraldes et al, 2023;Yeverino-Gutiérrez et al, 2020) En la cirrosis hepática presenta dos fases de la enfermedad, una compensada y descompensada, en la que cada una tiene diferentes cuadros clínicos; sin embargo, cabe recalcar que los pacientes en su fase descompensada tienen un alto riesgo de mortalidad en donde se evidencia la presencia de ascitis, encefalopatía hepática, hemorragia gastrointestinales e infección que conllevan a mal pronóstico de los pacientes (Kasper et al, 2022;Trebicka et al, 2020).…”
Section: Introductionunclassified
“…In 2017, there were 14330 deaths from alcoholic cirrhosis (2.05% of all deaths), a relative decrease of 21.27% compared to 2003, although deaths from alcoholic hepatitis have increased rapidly[ 44 ]. Another study analyzed trends in mortality from alcohol-related cirrhosis in Mexico from 2000-2017 and found a decrease in mortality in all age groups, with the associated mortality rate falling from 20.55 to 10.62 per 100000 for all populations during this period[ 45 ]. However, there has been a rapid increase in alcohol consumption in the United States and other regions in recent years, and consequently, the mortality rate from ALD has shown a marked increase[ 46 - 49 ].…”
Section: Current Epidemiology Of Liver Cirrhosismentioning
confidence: 99%